2016
DOI: 10.1016/j.prevetmed.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Farm characteristics and farmer perceptions associated with bovine tuberculosis incidents in areas of emerging endemic spread

Abstract: DisclaimerThe University of Gloucestershire has obtained warranties from all depositors as to their title in the material deposited and as to their right to deposit such material.The University of Gloucestershire makes no representation or warranties of commercial utility, title, or fitness for a particular purpose or any other warranty, express or implied in respect of any material deposited.The University of Gloucestershire makes no representation that the use of the materials will not infringe any patent, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 48 publications
2
26
2
Order By: Relevance
“…The greater variation in incidence between buffer areas is not surprising as they are geographically smaller than the central areas and contain fewer herds. The positive influence of the proportion dairy variable and the proportion of farms with more than one fragment of land on the association between culling and OTF‐W incidence in both intervention buffer areas is not unexpected as both are factors that have been found to be positively correlated with incidence in previous studies (Broughan et al., 2016; Goodchild & Clifton‐Hadley, 2001; Porphyre, Stevenson, & McKenzie, 2008). The sensitivity analysis demonstrates that there is considerable uncertainty around the estimates that cannot currently be explained.…”
Section: Discussionmentioning
confidence: 99%
“…The greater variation in incidence between buffer areas is not surprising as they are geographically smaller than the central areas and contain fewer herds. The positive influence of the proportion dairy variable and the proportion of farms with more than one fragment of land on the association between culling and OTF‐W incidence in both intervention buffer areas is not unexpected as both are factors that have been found to be positively correlated with incidence in previous studies (Broughan et al., 2016; Goodchild & Clifton‐Hadley, 2001; Porphyre, Stevenson, & McKenzie, 2008). The sensitivity analysis demonstrates that there is considerable uncertainty around the estimates that cannot currently be explained.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have identified several psychosocial factors in dairy farmers and veterinarians that might influence their decision on whether or not to implement biosecurity measures. Among these factors, it has been described that the attitude of farmers and veterinarians towards the implementation of biosecurity measures might be affected by the technical knowledge they have (Frössling & Nöremark, ; GarcĂ­a & Coelho, ; Toma, Low, Vosough, Matthews, & Stott, ), the individual experiences they have lived (Broughan et al, ), the importance they can attribute to risks (Renault, Humblet, et al, ), and the benefits they can obtain from measures implemented (Ciaravino et al, ). Moreover, their behaviour towards the implementation of biosecurity measures has also been related to their perceived social pressure to apply these measures (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…We expected that farms closest (i.e. 0-2 km) to the root farm would have the greatest effect on this risk as this would encompass potential contacts of cattle on shared boundaries and the risks from infected local wildlife [42]. However, the variable which best explained this risk was the proportion of farms with a bTB incident within a radius of 8 km.…”
Section: Discussionmentioning
confidence: 99%